(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The goal is to understand how children’s cognitive abilities affect how they comprehend television commercials and how they develop opinions about them. The goal of this essay is to examine how children’s perceptions of television advertising affect their subsequent purchasing choices. Methodology, design, and strategy - Experimental and descriptive methods have been used in this study. A literature study and deep conversations with pediatricians, marketers, and families of young kids are part of exploratory research. It was further developed by conducting a survey of kids between the ages of five and eleven whilst they were participating in class. The student teacher provided help with filling out the questionnaires, which had response possibilities presented in a visual form. Findings: There is a market for the advertised goods. Children’s perceptions of commercials have a significant impact on consumer demand for the things that are promoted. Additionally, the cognitive development of the various age groups results in the development of diverse attitudes toward the commercials. However, there are other strong elements outside ads that cause people to desire a product or brand. Investigation limitations/implications: The study was conducted among students in Delhi’s National Capital Region English-medium schools. As a result, the sample size is too limited. There hasn’t been any investigation into how the various purchase aspects interact with one another